447. Infant Microcephaly During the Zika Virus Epidemic in Dominican Republic, 2016–2017. (26th November 2018) - Peña, Farah; Pimentel, Raquel; Khosla, Shaveta; Mehta, Supriya; Brito, Maximo
Abstract: Background: Zika Virus infection (ZIKV) during pregnancy has been linked with fetal microcephaly. The purpose of this study was to describe the microcephaly cases that occurred during the ZIKV epidemic in Dominican Republic (DR) in 2016–2017. Methods: We analyzed surveillance data from DR National System of Epidemiologic Surveillance. The Intergrowth 21st Newborn size application tool was used to determine percentiles and z scores for head circumference (HC) by gestational age. We used linear and log-binomial regression for multivariate analyses of HC Z-score and severe microcephaly (HC of 0 percentile vs. >0 percentile), respectively. Results: Eighty-five infants were born with microcephaly due to ZIKV from June 2016 to March 2017. ZIKV IgM was positive in all 85 infants. Infants were 55% male and half were from the metropolitan area. Most (89%) received inpatient care and 13% had respiratory distress. One infant had a meningocele and one died soon after birth. Nearly half (47%) of mothers were known to have ZIKV and 45 (53%) mothers recalled having ZIKV symptoms during their pregnancy. Among these 45 women, the most common symptoms were rash (67%), fever (42%), and arthritis/arthralgia (24%). In two cases, ZIKV was reported in the father. Mean gestational age at birth was 37.8 weeks (±1.95 weeks), and 13% were born ≤36 weeks. The mean HC was 28.1 cm (SD ±2.1 cm). Severe microcephaly was detected in 67 (84%) cases, and 41% had an HC on the zero percentile for gestational age. Having insurance was associated with higher mean HC ( P = 0.01) while preterm birth was associated with lower mean HC ( P = 0.004). None of the variables were found to be significant predictors of HC z-score or severe microcephaly. Conclusion: There was substantial infant morbidity during the 2016–2017 epidemic. Most infants were born to asymptomatic women or women not reported to the Ministry during acute illness. More cases of microcephaly have been reported beyond the observation period which highlights the need for continued surveillance. Disclosures: All authors: No reported disclosures.